2017
DOI: 10.1103/physrevb.96.134105
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous dynamic characterization of charge and structural motion during ferroelectric switching

Abstract: Monitoring structural changes in ferroelectric thin films during electric field-induced polarization switching is important for a full microscopic understanding of the coupled motion of charges, atoms and domain walls. We combine standard ferroelectric test-cycles with time-resolved x-ray diffraction to investigate the response of a nanoscale ferroelectric oxide capacitor upon charging, discharging and switching. Piezoelectric strain develops during the electronic RC time constant and additionally during struc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…[30] The high resolution X-ray diffraction measurement showed that the film is c-axis oriented [28]. The reciprocal space map without applied external field was reported in a recent publication for a different electrode of the same sample [28]. The excellent FE properties of the device with an RC time constant of about 1 µs and a coercivity of about 4.5 V have been discussed in ref.…”
mentioning
confidence: 82%
See 4 more Smart Citations
“…[30] The high resolution X-ray diffraction measurement showed that the film is c-axis oriented [28]. The reciprocal space map without applied external field was reported in a recent publication for a different electrode of the same sample [28]. The excellent FE properties of the device with an RC time constant of about 1 µs and a coercivity of about 4.5 V have been discussed in ref.…”
mentioning
confidence: 82%
“…The typical full-width-at-half-maximum (FWHM) of the rocking curves was 0.3 • .The X-ray signal is sent to a timecorrelated single photon counting system (PicoHarp 300), which allows reconstructing the rocking curves at different delays by synchronizing the detector trigger with the rising edge of the electrical pulse. [30] The high resolution X-ray diffraction measurement showed that the film is c-axis oriented [28]. The reciprocal space map without applied external field was reported in a recent publication for a different electrode of the same sample [28].…”
mentioning
confidence: 85%
See 3 more Smart Citations